2014
DOI: 10.4314/sajas.v44i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and relationships of faecal worm egg count with objectively measured wool traits in the Tygerhoek Merino flock

Abstract: The costs of internal parasite control and treatment are potentially very high in grazing sheep. Faecal worm egg count (FEC) has been suggested as a suitable criterion for selection for resistance to nematode infestation in livestock. Genetic parameter estimates for FEC and its relationship with wool traits were assessed in the current study, using data from Merino sheep from a selection experiment maintained at Tygerhoek Research Farm. Data consisted of ~7 100 animals born between 1989 and 2010. Rectal faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
(93 reference statements)
4
27
0
Order By: Relevance
“…Extreme individual variation of FWEC is commonly reported in literature. Studies by Cloete et al (2007), Snyman (2007) and Matebesi-Ranthimo et al (2014) reported an individual variation for FWEC ranging from 0 to 13700, 0 to 87800 and 0 to 32700 epg wet faeces, respectively. In a study by Khusro et al (2004), means for FWEC were 736 for hoggets and 779 for yearling Merino sheep, while the individual variation for FWEC ranged from 0 to 50000 epg in both age groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extreme individual variation of FWEC is commonly reported in literature. Studies by Cloete et al (2007), Snyman (2007) and Matebesi-Ranthimo et al (2014) reported an individual variation for FWEC ranging from 0 to 13700, 0 to 87800 and 0 to 32700 epg wet faeces, respectively. In a study by Khusro et al (2004), means for FWEC were 736 for hoggets and 779 for yearling Merino sheep, while the individual variation for FWEC ranged from 0 to 50000 epg in both age groups.…”
Section: Discussionmentioning
confidence: 99%
“…present as major species and Haemonchus contortus as a minor species (Reinecke et al, 1987). Individual faecal samples were analysed at Stellenbosch Provincial Veterinary Laboratory, using the McMaster technique, with a sensitivity of 100 eggs per gram (epg) of wet faeces (Van Schalkwyk et al, 1994;Matebesi-Ranthimo et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations